PENERAPAN USER INTERFACE DAN USER EXPERIENCE PADA SIPETAN (SISTEM PEMETAAN TANAH PERTANIAN) KABUPATEN MALANG - Naja, M Muttaqi Saifun; Budianto, Alexius Endy; Moh Ahsan (Prodi Teknik Informatika, Fakultas Sains dan Teknologi, 2025)
Urek-Urek Village with all its community diversity requires overlapping in terms of economic equality, especially in terms of fertilizer subsidies. The problem is caused by inaccurate land data so that the asset data used as the basis for distributing subsidies affects the amount of subsidies received which does not match field conditions. The implementation of subsidy management so far has been based on conventional techniques so that a capable system is needed to accommodate the problems. This study uses a user-centered design approach as the basis for designing the Land Mapping Information System (SIPETAN) application design. This study will concentrate on two main problems: the SIPETAN user interface design process and the analysis of SIPETAN users in providing agricultural information to farmers in Urek-Urek Village. This study shows practical applications that can be used for the land data collection process and to help the Urek-Urek Village organization manage it.